PROBLEMS OF DIGITIZATION OF AGRICULTURE AND USING INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE MANAGEMENT OF THE AGRO-INDUSTRIAL COMPLEX - Dokholyan,; Babaeva,; Baliyants,; Eminova, (Revista Inclusiones, 2020)
The manuscript presented addresses the study of problems related to the commitment to digitization of agriculture of the Russian Federation from the viewpoint of the current state of available allowances for the acquisition and fastest wide implementation of the necessary information technologies that will allow for a qualitative breakthrough in solving different issues with their help (both grand-scale and specific) issues to make managerial decisions in the economic and technological spheres of the agro-industrial complex of the North Caucasian Federal District.